Fitoakumulasi Logam Ni dan Zn Dalam Tumbuhan Nipah (Nypa fruticans) Di Sungai Tallo Makassar - La Nafie, Nursiah; Liong, Syarifuddin; Arifin, Rizda (Indonesian Journal of Chemical Research, 2019)
Research on phytoaccumulation of Ni and Zn in Nypa fruticans plants at Tallo River has been done to know the capability of Nypa fruticans for accumulating Ni and Zn. Water, sediment, and plant tissue samples were taken at five stations on the Tallo River using a cutting tool and pipe paralon. Sediment was digested with concentrated HNO3 while plants tissue using HNO3 6M, then analyzed by ICP EOS Shimadzu 9000. The results showed the average concentration of Ni inside part of the plant from station 1, 2, 3, 4 and 5 in order following 21.759,03 ppm, 19.056,03 ppm; 36.806,25 ppm; 10.736,66 ppm dan 13.849,25 ppm. Average concentration of Zn inside the plant from station 1, 2, 3, 4 and 5 in order following 1.319,60 ppm; 1.362,93 ppm; 2.053,46 ppm; 1.591,60 ppm; dan 1.474,09 ppm. Accumulation of Zn and Ni in Nypa fruticans is grouped as hyperaccumulation plant because the ability of accumulation Ni bigger than 10.000 mg/kg and hyperaccumulation towards Zn because able to accumulate Zn bigger than 10 mg/kg. BCF and TF value show that Nypa fruticans naturally able to be used as an phytoremediation plant towards Ni and Zn, especially phytoextraction and rhizofiltration.